Psychosocially Supporative Design - As a Theory and Model to Promote Health (A Letter to Editor) - Dilani, Alan (Sulaimani Journal for Pure and Applied Sciences, 2007)
The board of JZS has received a letter from Prof.Alan Dilani, who is from Kurdistan of Iran and a Swedish Citizen an 12/04/2007. The following is part of his letter: I will send you an article please find as attachment, it has been newly published in the book of the year of International Hospital Federation dealing with Health promotion and is very relevant for Kurdistan. You are free to publish in the next number. I wish you again all the best for you and Dr.Ali Saeed Mohammad to develop University of Sulaimani as a top academic in the region.